Husband's Unemployment and Wife's Labor Supply: The Added Worker Effect across Europe - Julia Bredtmann; Sebastian Otten; Christian Rulff (Institute of Labor Economics (IZA), 2017)
This paper investigates the responsiveness of women's labor supply to their husband's job loss – the so-called added worker effect. We contribute to the literature by taking an explicit internationally comparative perspective and analyze the variation of the added worker effect across welfare regimes. Using longitudinal data from the European Union Statistics on Income and Living Conditions (EU-SILC) covering 28 European countries from 2004 to 2013, we find evidence for the existence of an added worker effect. However, our results also reveal that the added worker effect varies over both the business cycle and the different welfare regimes within Europe.
Keywords: J22; J64; J82; 330; added worker effect; labor supply; unemployment; cross-country analysis